2012
DOI: 10.1007/s00296-012-2585-z
|View full text |Cite
|
Sign up to set email alerts
|

Is Helicobacter pylori infection a risk factor for disease severity in systemic sclerosis?

Abstract: Helicobacter pylori (H. pylori) is suspected to be one of the factors triggering systemic sclerosis (SSc). Data on the possible role of H. pylori are lacking. The aim of this study was to assess the effect of H. pylori infection in SSc patients. Forty-two SSc patients without dyspeptic symptoms were recruited--26 were H. pylori-positive and 16 were H. pylori-negative on the basis of invasive test. We evaluated the disease severity using clinical and laboratory parameters according to the Medsger Severity Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
0
17
0
2
Order By: Relevance
“…Evidence that a strong genetic component is linked to GIT SSc is highlighted by a study demonstrating that Canadian North American Native patients had more severe GIT involvement compared to Caucasian Americans . Studies have also demonstrated a high prevalence of Helicobacter pylori infection in SSc patients, supporting a role for an infectious aetiology . Fibroproliferative vasculopathy, immune dysfunction and fibrosis have been postulated as pathogenic mechanisms of GIT dysfunction and structural alterations in SSc (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence that a strong genetic component is linked to GIT SSc is highlighted by a study demonstrating that Canadian North American Native patients had more severe GIT involvement compared to Caucasian Americans . Studies have also demonstrated a high prevalence of Helicobacter pylori infection in SSc patients, supporting a role for an infectious aetiology . Fibroproliferative vasculopathy, immune dysfunction and fibrosis have been postulated as pathogenic mechanisms of GIT dysfunction and structural alterations in SSc (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study identified some haplotypes in an American native population (Choctaw Indians) strongly associated with SSc and more severe progression of this disease (HLA-DRB1*1602, DQB1*0301 and DQA1*0501) [8]. Some studies have also reported high prevalence of Helicobacter infection in SSc patients, supporting the hypothesis of infectious aetiology [9]. Smoking has been identified as the only environmental factor associated with increased severity of GIT symptoms in SSc [10].…”
Section: Introductionmentioning
confidence: 90%
“…Identify pathoorganisms triggering the disease (e.g. Helicobacter pylori[9]) Identify the insult/toxin triggering the disease (smoking, exposition to toxic substances, etc. )…”
mentioning
confidence: 99%
“…В относительно недавнем исследовании M. Radic и соавт. [48] выявили четкую связь между активностью ПСС (в част-ности, выраженностью кожного счета) и наличием H. pylori.…”
Section: а у т о и м м у н н ы е з а б о л е в а н и я и а с с о ц и unclassified